EVALUASI BAKTERI INDIKATOR SANITASI DI SEPANJANG RANTAI DISTRIBUSI ES BATU DI BOGOR - Antung Sima Firlieyanti (Jurnal Ilmu Pertanian Indonesia, 2006)
Ice was never considered to be of microbiological concern, due to it's low temperature. However, this perception is contradictive with a number research that shows several outbreaks of enteric Illness caused by ice. Evaluation of microbiological quality of ica In Bogor, emphasize on the presence of sanitation indicator bacteria (coliform fecal and non fecal) is associated with hygiene and sanitation implemantation on Ice handling. The presence of sanitation indicator bacteria on ice Is an Indication of poor hygiene on Ice handling, and also as an indicator of the presence of fecal pathogenic bacteria that can be harmful since they can cause foodborne diseases. The objective of this research is to examine the microbiological quality of ice through out Its distribution chain In Bogor, with coliform presence as the criteria. A total of 31 samples were analysed, consisted of 4 samples from ice manufactures, 6 samples from distributors ('depot’), and 21 samples from ice vendors. The result showed the total plate count of the samples are in the range between 2.8xl02 CFU/ml to 1.1x106 CFU/ml, while coliform were 1.5x102 MPN/100 ml to 1.2x106 MPN/100 ml. There were 31 samples (100%) coliform positive, 14 samples (45%) fecal coliform positive, 31 samples (100%) non fecal coliform positive, and 3 samples (10%) E.coli positive. The results shawed that ice cubes in Bogor area did not meet the microbiological criteria specified In SNI and Kepmenkes (coliform and E. coli absence in 100 ml) indicating of poor hygiene of Ice handling In Bogor.